1995
DOI: 10.1007/bf01705408
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response syndrome, sepsis, severe sepsis and septic shock: Incidence, morbidities and outcomes in surgical ICU patients

Abstract: Almost everyone in the SICU had SIRS. Therefore, because of its poor specificity, SIRS was not helpful predicting severe sepsis and septic shock. Patients who developed sepsis or severe sepsis had higher crude mortality and length of stay than those who did not. Studies designed to identify those who develop complications of SIRS would be very useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
2
13

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(178 citation statements)
references
References 17 publications
8
155
2
13
Order By: Relevance
“…[17][18][19][20][21][22][23][24] Previously published data on the test characteristics of SIRS have largely focused on the SIRS score at the time of presentation to the emergency department or upon admission to the medical floor or ICU. Since our patients are often admitted for prolonged hospital stays (30 day planned admissions) …”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Previously published data on the test characteristics of SIRS have largely focused on the SIRS score at the time of presentation to the emergency department or upon admission to the medical floor or ICU. Since our patients are often admitted for prolonged hospital stays (30 day planned admissions) …”
Section: Discussionmentioning
confidence: 99%
“…This likely represents the independent association between SIRS and organ dysfunction with the risk for mortality (27,31,32).…”
Section: Discussionmentioning
confidence: 95%
“…One review of 39 EWSs reported PPVs ranging from 13.5-26.1% (34), and another review of 25 systems reported a median PPV of 36.7% with interquartile range 29.3-43.8% (34). PPV was not reported for several of the most elegant and well-studied EWSs (22,23,25,32). From the perspective of bedside clinicians and rapid response team members, the efficiency of an alert system is strongly influenced by the PPV, because a poor PPV translates to frequent false alerts.…”
Section: * Our Data Indicate That Rrt Activation Would Occur About Twmentioning
confidence: 99%
“…Different studies have shown that the incidence of SIRS is quite high in critical patients in general. For example, Pittet et al [44] presented a SIRS incidence of up to 93% in critical care patients, while Rangel et al showed an incidence of 68% [43]. The latter study also shows that 25% of patients with SIRS developed a Sepsis, 18% presented Severe Sepsis, and 4% of them, Septic Shock.…”
Section: Quantitative Analysis Of the Prognosis Of Sepsismentioning
confidence: 92%